Placement of lord Ganesha on the doorway - Ghosh, Ayan (2023)
A common feature at all the temples and even private homes in Maharashtra is the presence of a Ganesha figure at the top of the entrance or doorway. Lord Ganesha is venerated as the remover of obstacles, and his presence is considered auspicious and a harbinger of good luck.